Excellent energy storage properties over a wide temperature range under low driving electric fields in NBT-BSN lead-free relaxor ferroelectric ceramics. Issue 4 (15th February 2021) - Fan, Zhenhao; Yu, Yuxi; Huang, Jie; Zhang, Qingfeng; Lu, Yinmei; He, Yunbin
Abstract: To develop environment-friendly dielectric capacitors with low working electric field and wide useable temperature, in this work, we fabricate (1- x )Na0.46 Bi0.54 TiO3 - x BaSnO3 ((1- x )NBT- x BSN) lead-free relaxor ferroelectric ceramics by adding BaSnO3 into Na0.46 Bi0.54 TiO3 matrix. BSN exhibits slim polarization-electric field ( P-E ) loops, small remnant polarization ( P r ) and good temperature stability because of its room-temperature paraelectric characteristics, and has different cation ionic radii with Na0.46 Bi0.54 TiO3 . Therefore, when BSN is introduced into NBT, the relaxor behavior of the (1- x )NBT- x BSN ceramics is more pronounced and the P - E loops are much slimmer. Besides, because the substitution of Ba 2+ ions with higher valence for Na + ions neutralizes the hole carriers, which are caused by the volatilization of Na2 O, the resistivity and breakdown strength are improved with increasing BSN content. As a consequence, at x  = 0.30, the ceramic exhibits simultaneously a large recoverable energy density ( W rec ) of 1.51 J/cm 3 and high energy efficiency ( η ) of 81.2% at a low driving electric field of 145.3 kV/cm because of the collaborative enhancement effect of the high breakdown strength and low remnant polarization. More interestingly, variations of the W rec and the η for this kind of ceramic are respectively as small as 10% and 0.8% over a wide temperature range of 20–140 °C, demonstrating superior temperature stability. In this report, we provide a new and efficient way for designing and fabricating environment-friendly dielectric capacitors with good reliability and superior high-temperature energy storage capacity.